Integrity at stake: confronting “publish or perish” in the developing world and emerging economies - Vasconez-Gonzalez, Jorge; Izquierdo-Condoy, Juan S.; Naranjo-Lara, Patricio; Garcia-Bereguiain, Miguel Ángel; Ortiz-Prado, Esteban (Frontiers in Medicine, 2024)
From its inception, the scientific method has been instrumental in the advancement of various societies, serving not only to resolve complex problems but also as a fundamental tool for the generation of knowledge through theories and propositions (1-3). These scholarly contributions have significantly impacted the realms of invention and have markedly improved the quality of life across the globe. Over the last centuries, scientific publishing has witnessed a profound evolution, expanding from a modest collection of 10 journals in the 17th century, to an extensive network of over 100,000 journals by the close of the 20th century (4). This remarkable growth highlights the essential role that publishing plays in the progress of science; facilitating the widespread dissemination of groundbreaking of innovative ideas, findings, and theories (5). Consequently, the act of publishing has become a pivotal component of the activities that researchers must fulfill, with universities increasingly regarding scientific papers as critical metrics for evaluation and ranking within the academic community (6,7) .In this landscape, however, the pressures of "publish or perish" have catalyzed the emergence of unethical practices within the academic community(8). It is well known by the scientific community worldwide that there are several forums in the internet where trade of authorships happened. Also, the so called paper mills, are organizations that using Artificial Intelligence (AI), and other tools to produce high amounts of publications, with the solely purpose of offering authorship for sale for as little as 200 USD, without making any substantive contribution to the article (9).